A Framework to Examine the Role of Epigenetics in Health Disparities among Native Americans. (9th December 2013) - Brockie, Teresa N.; Heinzelmann, Morgan; Gill, Jessica
Abstract : Background . Native Americans disproportionately experience adverse childhood experiences (ACEs) as well as health disparities, including high rates of posttraumatic stress, depression, and substance abuse. Many ACEs have been linked to methylation changes in genes that regulate the stress response, suggesting that these molecular changes may underlie the risk for psychiatric disorders related to ACEs. Methods . We reviewed published studies to provide evidence that ACE-related methylation changes contribute to health disparities in Native Americans. This framework may be adapted to understand how ACEs may result in health disparities in other racial/ethnic groups. Findings . Here we provide evidence that links ACEs to methylation differences in genes that regulate the stress response. Psychiatric disorders are also associated with methylation differences in endocrine, immune, and neurotransmitter genes that serve to regulate the stress response and are linked to psychiatric symptoms and medical morbidity. We provide evidence linking ACEs to these epigenetic modifications, suggesting that ACEs contribute to the vulnerability for developing psychiatric disorders in Native Americans. Conclusion . Additional studies are needed to better understand how ACEs contribute to health and well-being. These studies may inform future interventions to address these serious risks and promote the health and well-being of Native Americans.